Discovery of a series of dimethoxybenzene FGFR inhibitors with 5H-pyrrolo[2,3-b]pyrazine scaffold: structure-activity relationship, crystal structural characterization and in vivo study - Peng Wei; Bo Liu; Ruifeng Wang; Yinglei Gao; Lanlan Li; Yuchi Ma; Zhiwei Qian; Yuelei Chen; Maosheng Cheng; Meiyu Geng; Jingkang Shen; Dongmei Zhao; et al. (Elsevier, 2019)
Genomic alterations are commonly found in the signaling pathways of fibroblast growth factor receptors (FGFRs). Although there is no selective FGFR inhibitors in market, several promising inhibitors have been investigated in clinical trials, and showed encouraging efficacies in patients. By designing a hybrid between the FGFR-selectivity-enhancing motif dimethoxybenzene group and our previously identified novel scaffold, we discovered a new series of potent FGFR inhibitors, with the best one showing sub-nanomolar enzymatic activity. After several round of optimization and with the solved crystal structure, detailed structureactivity relationship was elaborated. Together with in vitro metabolic stability tests and in vivo pharmacokinetic profiling, a representative compound (35) was selected and tested in xenograft mouse model, and the result demonstrated that inhibitor 35 was effective against tumors with FGFR genetic alterations, exhibiting potential for further development. KEY WORDS: Fibroblast growth factor, Tyrosine kinase receptor, Structure-based, Crystallography, Selectivity, Hybrid, 5-Hydrosulfonyl-5H-pyrrolo[2,3-b]pyrazine, Inhibitor